La vida del Lazarillo de Tormes y de sus fortunas y adversidades - Blecua, Alberto (Clásicos Castalia, 2012)
Presents the text of the classic novel in which young rogue Lazaro recounts his adventures and describes how he outwits his series of masters, with modernized spelling, an explanatory introduction, notes, and activities.